The Tourism Awareness Education in Supporting The Tourism Development of Muaro Jambi Temple - A D Nugroho (NAROTAMA UNIVERSITY, Indonesia, 2021)
Muaro Jambi Temple is one of the largest Hindu-Buddhist temple complexes in Southeast Asia, in the residential area of Jambi Malay community. In the beginning, the community assumed that the existence of the temple complex was only a historical heritage, which was nothing more than ancient buildings. They haven't realized that the historical heritage is an international tourism destination that has the potential to improve the economy of local communities. With the efforts of some parties to educate, to provide tourism awareness education to the community, eventually grew the awareness that the existence of the temple can be a new source of income to improve the welfare of their lives. Not a few local community who initially worked as a garden farmer, gradually turned into an entrepreneurs of lodging, restaurants, souvenirs, entertainment, and others. Surely the phenomenon becomes one of the attractiveness for foreign and domestic tourists to visit Muaro Jambi temple. Thus, the tourism awareness education that is done play a role in supporting tourism development of Muaro Jambi Temple.